Accelerating action against child labour : global report under the follow-up to the ILO Declaration on Fundamental Principles and Rights at Work - International Labour Office; International Labour Conference 2010 : Geneva, Switzerland) (Geneva : International Labour Office, 2010)
In its quadrennial Global Report on child labour, the ILO says that the global number of child labourers had declined from 222 million to 215 million, or 3 per cent, over the period 2004 to 2008, representing a "slowing down of the global pace of reduction." The report also expresses concern that the global economic crisis could "further brake" progress toward the goal of eliminating the worst forms of child labour by 2016.
pt. 1. A dynamic global picture -- pt. 2. Important achievements on the road to 2016 -- pt. 3. Turning challenges into opportunities -- pt. 4. Accelerating progress towards 2016.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Child labor -- Prevention; Children -- Legal status, laws, etc; Forced labor -- Prevention; Children's rights; Human rights; Human Rights; Enfants -- Droits; Droits de l'homme (Droit international); BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Children -- Legal status, laws, etc; Children's rights; Human rights